2021
DOI: 10.1590/acb360208
|View full text |Cite
|
Sign up to set email alerts
|

Techniques of orthotopic renal transplantation in pigs. One donor to two recipients via inverted grafting

Abstract: Purpose Although transplanting two kidneys from a single donor to two recipients has some advantages, the right and left kidneys are not anatomically identical; thus, a surgical procedure considering the anatomical features of the donor kidneys is needed when transplanting them into the opposite renal fossae. Based on vast experience, the surgical details of pig orthotopic kidney transplantation from one donor to two recipients was reported. Methods When the right kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…However, with the conventional method, the transplanted kidney turned dark red, and the presence of venous congestion was suspected. These findings and the postoperative course suggested that transplants by the conventional method may be susceptible to torsion of the venous anastomosis due to body movements, which led us to decide on orthotopic transplantation to the natural locations of the renal artery and vein, which we previously reported in a pig-to-pig renal transplant 10 . The ingenuity of the orthotopic transplant method developed in this study lies in the use of the recipient's renal artery in xenotransplantation without immunosuppression; rather, vascular insufficiency occurred, as indicated by the findings of glomerular collapse and dissection of the renal tubules from the basal membrane (Figs.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…However, with the conventional method, the transplanted kidney turned dark red, and the presence of venous congestion was suspected. These findings and the postoperative course suggested that transplants by the conventional method may be susceptible to torsion of the venous anastomosis due to body movements, which led us to decide on orthotopic transplantation to the natural locations of the renal artery and vein, which we previously reported in a pig-to-pig renal transplant 10 . The ingenuity of the orthotopic transplant method developed in this study lies in the use of the recipient's renal artery in xenotransplantation without immunosuppression; rather, vascular insufficiency occurred, as indicated by the findings of glomerular collapse and dissection of the renal tubules from the basal membrane (Figs.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, all renal xenotransplant experiments were approved by the animal ethics committee of the Jikei University School of Medicine (approval number: 2020-055). An expert surgeon (E.K), who have had more than fifty experiences of pig kidney transplantation, conducted the series of experiments 10 , 11 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of the similar size of the kidney in swine and humans, the pig model is frequently chosen for research in the field of kidney transplantation and also for surgical training [59,80].…”
Section: Kidney Transplantationmentioning
confidence: 99%